(untitled) (Bangladesh Agronomy Journal, 2024)
Ten mung bean accessions collected from Bangladesh Agricultural Research Institute were exposed to two salinity levels (control and 8 dS m−1) to observe the sensitivity of their germination and early seedling traits. The observations were recorded on germination percentage, rate of germination, coefficient of germination, shoot length, root length and seedling dry weight. The accessions, salinity levels and their interaction exhibited significant differences for all the traits. The mean performance of all the traits reduced under salt stress as compared to control. Salt tolerant accessions showed less reduction in their germination and seedling traits under salinity than the other accessions tested. Considering salt tolerance index (STI) based on seedling dry weight, the order of tolerance was BD- 6882 > BD-10022 > BD-10024 > BD-10026 > BD-10023 > BD-10027 > BD-6885 > BD-6887 > BD- 6884 > BD-6875. Based on relative total dry weight (RTDW), three accessions viz. BD-6882, BD- 10022 and BD-10024 were identified as salt tolerant and other seven as moderately salt tolerant. The identified salt tolerant accessions could be a useful stock for further breeding programs to develop salt tolerant mung bean genotype of considerable economic value. Bangladesh Agron. J. 2024, 26(2): 16-26